ENGLISH LEARNING STRATEGIES IN THE IMPLEMENTATION OF THE 2013 CURRICULUM FOR CLASS VII AT SMP NEGERI 2 MUNTHE - Br. Perangin-Angin, Revina Elisa (BRIGHT VISION Journal of Language and Education, 2022)
The aim of this research is to see how English learning strategies are implemented in the implementation of the 2013 class VII curriculum at SMP Negeri 2 Munthe. This research uses qualitative research with a descriptive approach, this research uses qualitative research. Referring to Strauss and Corbin. The subject of this research was carried out at SMP N 2 Munthe in class VII. Where it was found that the learning strategies applied by English teachers were implementing contextual and scientific learning strategies. There are several obstacles in implementing the 2013 curriculum.